2019
DOI: 10.1016/j.aninu.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of Bacillus coagulans or yeast hydrolysates on growth performance, antioxidant activity, cytokines and intestinal microflora of growing-finishing pigs

Abstract: This study was to investigate the effects of dietary supplementation of Bacillus coagulans (BC) and yeast hydrolysates (YH) on growth performance, antioxidant activity, cytokines and intestinal microflora of growing-finishing pigs. Thirty-six barrows (initial BW = 26.87 ± 2.65 kg) were assigned randomly to 3 treatments with 4 replicates, 3 pigs per replicate. Pigs in the control group (CON) were fed a basal diet, and the diets for the other 2 groups were the basal diet plus BC at 200 mg/kg and the basal diet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
3
28
0
2
Order By: Relevance
“…Our results indicated that YC supplementation significantly increased lysozyme and T-AOC in serum and reduced serum AST. Similarly, a previous study showed that supplemented yeast hydrolysates tended to increase serum T-AOC (Fu et al, 2019). Thus, improvements in serum T-AOC and lysozyme activity indicated that YC administration can improve antioxidant capacity and enhance innate immunity (Min et al, 2015) of layers.…”
Section: Discussionmentioning
confidence: 63%
“…Our results indicated that YC supplementation significantly increased lysozyme and T-AOC in serum and reduced serum AST. Similarly, a previous study showed that supplemented yeast hydrolysates tended to increase serum T-AOC (Fu et al, 2019). Thus, improvements in serum T-AOC and lysozyme activity indicated that YC administration can improve antioxidant capacity and enhance innate immunity (Min et al, 2015) of layers.…”
Section: Discussionmentioning
confidence: 63%
“…Yeast-derived products, such as yeast cell call ( Wang et al., 2017 ; Ma et al., 2020 ), yeast hydrolysate ( Fu et al, 2019 ; Rahimnejad et al., 2020 ), dried yeast extracts ( Kim et al., 2019b ), and yeast culture ( Samarasinghe et al, 2004 ; Sun et al., 2020 ), are natural feed additives that have been used in animals for decades. Supplementing animals with yeast cell wall improved the growth performance, digestive function, and antioxidant capacity of animals ( Li et al., 2016 ; Wang et al., 2017 ; Salinas-Chavira et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The total feed intake of every group was counted from the 17 th to 60 th day. At the end of the feeding experiment, each experimental lamb was weighed, and the feed conversion ratio (F/G) was calculated by using the following equation [ 46 ]: …”
Section: Methodsmentioning
confidence: 99%